SYNTHESIS OF LIQUID ORGANIC FERTILIZER BASED ON CHICKEN MANURE USING BIOSCA AND FUNGUS BIOACTIVATOR Trichoderma harzianum - Rahmad, Rahmad; Karim, Abdul; La Nafie, Nursiah; Jayadi, Muhammad (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Production of liquid organic fertilizer from chicken feces with addition bioaktivator Biosca and Trichoderma harzianum fungus aims to determine the influence of time against pH and macro elements (N, P, and K), analyze the influence and determine the bioactivator composition against pH, macro element content, growth and production of tomato plants. The method of making this liquid organic fertilizer is chicken feces dissolved using water in a composter, then composted with addition of bioactivator which is consisting B1 (40 mL Biosca), B2 (40 mL T. harzianum), B3 (10 mL Biosca + 30 mL T. harzianum), B4 (20 mL Biosca + 20 mL T. harzianum) and B5 (30 mL Biosca + 10 mL T. harzianum). Composting is done by time variations of 7 days (M1), 14 days (M2) and 21 days (M3). The result of research shows that the process of making organic liquid fertilizer with time variation of composting and effective bioactivator composition in increasing macro element level and good pH is B5 with 21 days of composting time. The influence of bioactivator composition against pH and macro element indicator is showed by value of N: 5,33%, P: 2,41%, K: 1,34% at pH: 7,1. While the influence against tomato plants on the observation at the 10th week is for the growth of plant height: 197,7 cm, average of plant diameter: 16,27 mm, average of leaf production: 41 sheets, and for the average of fruit production: 32 pieces, average of fruit weight: 32,4 g.